2020
DOI: 10.1021/acs.chemrev.0c00069
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Syntheses of Noncanonical Nucleosides and Nucleotides

Abstract: The origin of nucleotides is a major question in origins-of-life research. Given the central importance of RNA in biology and the influential RNA World hypothesis, a great deal of this research has focused on finding possible prebiotic syntheses of the four canonical nucleotides of coding RNA. However, the use of nucleotides in other roles across the tree of life might be evidence that nucleotides have been used in noncoding roles for even longer than RNA has been used as a genetic polymer. Likewise, it is pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 115 publications
0
41
0
1
Order By: Relevance
“…To further reinforce its prebiotic relevance, we have shown that D could have been formed on early Earth alongside A through a transglycosylation reaction. Alternative syntheses of purine (deoxy)nucleosides raise the prospect that D might also be a product of these alternative chemistries, perhaps in more significant yields 15 , 17 , 24 , 49 , 50 . Given its only moderately lower photostability relative to A, D could survive long enough in a UV-rich environment to be incorporated into oligomers and play a further role in enzyme-free DNA self-replication.…”
Section: Discussionmentioning
confidence: 99%
“…To further reinforce its prebiotic relevance, we have shown that D could have been formed on early Earth alongside A through a transglycosylation reaction. Alternative syntheses of purine (deoxy)nucleosides raise the prospect that D might also be a product of these alternative chemistries, perhaps in more significant yields 15 , 17 , 24 , 49 , 50 . Given its only moderately lower photostability relative to A, D could survive long enough in a UV-rich environment to be incorporated into oligomers and play a further role in enzyme-free DNA self-replication.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of DNA as the information storage molecule for life today is common knowledge, but that role emerged well after the IDA. Here, we simply point out that while RNA has a special role in the origin of Darwinian life, several authors have proposed that RNA and DNA may well have emerged simultaneously, perhaps forming chimeric RNA/DNA structures (see review in [ 68 ]), with a range of nucleotides having prebiotic non-coding roles [ 193 ]. We note that while catalytic DNAs have been synthesized [ 194 ], there are no DNA catalysts in living cells.…”
Section: The Microchamber Complex Scenariomentioning
confidence: 99%
“…Research studies making use of the thermal decomposition of urea as a means to control the pH during the synthesis of saponites include those of Besselink et al [ 40 ], Prihod’ko et al [ 47 ], Sychev and Prihod’ko [ 37 ], Xue and Pinnavaia [ 38 ], and Yu et al [ 48 ]. Given that urea has more potential than just controlling the pH in clay mineral synthesis as it is a potential precursor of nucleobases and related molecules and a promoter of phosphorylation [ 25 , 26 , 49 ], the urea-assisted synthesis of saponites might be useful as starting point in extending research into urea assisting the synthesis of clay minerals while at the same time providing a source of precursors for nucleobases formation.…”
Section: Saponite Synthesis and Characterizationmentioning
confidence: 99%
“…Its structure and properties make it a potentially good starting material for the synthesis of nucleobases and related molecules [25,26]. It has been shown to promote phosphorylation reactions [25,26]. Moreover, it was able to catalyze formation of saponite clays in only 20 h under relatively mild conditions [27].…”
Section: Introductionmentioning
confidence: 99%